THE IMPACT OF WHV (WORK HOLIDAY VISA) ON INTERNATIONAL LAW - M. Rizky Zain (Polteknik Imigrasi, 2023)
The Minister of Trade, Enggartiasto Lukita held a collaboration program with the Australian Minister of Trade, Simon Birmingham, the Indonesia-Australia Comprehensive Trade Agreement (IA-CEPA). One of the results of the signing of a free trade agreement namely Australia with Indonesia is the addition of working and holiday visa quotas in Australia for eligible Indonesian youth. The Australian Government has confirmed that there will be an increase in the number of Working Holiday Visa (WHV) quotas prepared as part of the agreement. The total quota will reach 4,100 from the previous 1,000 in the first year, with an increase of 5,000 in six years. There are no research results that explain how the WHV is against the perspective of international law because this is a new thing. This is a challenge to discuss and how it affects the world. The method used in the preparation of this journal is the normative-juridical method. The program must be utilized properly because it will have a positive impact on Indonesia and notify the public, especially young Indonesians who want to go to Australia in order to take education and work